2015
DOI: 10.1002/ceas.12012
|View full text |Cite
|
Sign up to set email alerts
|

Gatekeeping Ourselves: Counselor Educators' Knowledge of Colleagues' Problematic Behaviors

Abstract: Counselor educators in programs accredited by the Council for Accreditation of Counseling and Related Educational Programs (N = 335) were surveyed about their knowledge of colleagues' problems of professional competency (PPC). Findings suggest most participants are aware of colleagues with PPC. Professional behavior standards must be developed for those entrusted with counselor preparation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…The findings from this study show that the majority (68.1%) of doctoral students reported that they had observed peers with PPC in their training programs and that they were likely to be influenced by peers' nonacademic characteristics (e.g., inability to regulate emotions, unprofessional behaviors). The results of this study mirror other studies on counseling students with PPC (Brown-Rice & Furr, 2013Foster, Leppma, & Hutchinson, 2014), in which PPC was identified as a major concern among master's-level students. This is the first study to extensively examine this issue among doctoral students.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The findings from this study show that the majority (68.1%) of doctoral students reported that they had observed peers with PPC in their training programs and that they were likely to be influenced by peers' nonacademic characteristics (e.g., inability to regulate emotions, unprofessional behaviors). The results of this study mirror other studies on counseling students with PPC (Brown-Rice & Furr, 2013Foster, Leppma, & Hutchinson, 2014), in which PPC was identified as a major concern among master's-level students. This is the first study to extensively examine this issue among doctoral students.…”
Section: Discussionsupporting
confidence: 85%
“…The Problems of Professional Competency Survey-Doctoral (PPCS-D) evolved from the Problems of Professional Competency Survey (PPCS-MS) used to evaluate master's students' knowledge of peers with PPC (Brown-Rice & Furr, 2013). We established the content validity and reliability of the original instrument through an expert review, pilot studies, and principal component analysis (see Brown-Rice & Furr, 2013). We altered the language of items from the PPCS-MS for the PPCS-D to fit the doctoral in their program who exhibited problematic behavior.…”
Section: Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…After removing program duplicates and surveys exceeding the threshold for incomplete items, 73 surveys remained in the sample, resulting in a 32% program response rate. This response rate is commensurate with other counselor education program survey response rates ranging from 26% to 33% (Brown-Rice & Furr, 2015;Swank & Smith-Adcock, 2014). Similarly, the response rate aligns with the 34% average online response rate found across 207 articles from four counseling journals (Poynton, DeFouw, & Morizio, 2019).…”
Section: Methodssupporting
confidence: 76%
“…However, a 22% response rate is typical for online surveys (Nulty, 2008), and the sample size provided enough statistical power to conduct the analyses given the large amount of variance explained in each of the models. Second, the sample primarily included faculty who identified as female and White, but these demographics are representative of most studies within counselor education (e.g., Brown‐Rice & Furr, 2015; Neuer Colburn, Grothaus, Hays, & Milliken, 2016). Third, given the lack of demographic information on nonrespondents, we were unable to explore whether they differed from respondents on any demographic information.…”
Section: Discussionmentioning
confidence: 99%